Preschool-based mother-child emotional preparation program improves emotional connection, behavior regulation in the home and classroom: a randomized controlled trial - Welch, Martha G.; Ludwig, Robert J.; Hane, Amie A.; Austin, Judy; Markowitz, Elizabeth S.; Jaffe, Marc E.; Myers, Michael M. (Frontiers in Child and Adolescent Psychiatry, 2023)
Introduction Based on the theory that increasing emotional connection and reducing emotional stress between mother and child at home will reduce dysregulated behavior in the classroom, we tested a novel family-based school intervention aimed at facilitating mother-child emotional connection. This question has gained great importance following the COVID-19 pandemic, as child mental health has been declared a national emergency. Methods Subjects were randomized into two groups; one (Control: n = 32) receiving the standard curriculum in a large community-based preschool education program, and another (MCEP) receiving the standard curriculum plus the Mother Child Emotional Preparation Program (MCEP: n = 30). Two to eight MCEP mother-child pairs participated in eight elective weekly 2-h group sessions over a 16-week period. During the 2-h sessions, the pairs were engaged in face to face calming sessions. At 6 months post-enrollment, we assessed mother-child emotional connection on the Welch Emotional Connection Screen (WECS). In addition, mothers and teachers completed validated questionnaires and instruments. Results We found that the percentage of MCEP mother-child pairs who became emotionally connected at 6 months was five-fold higher than Control pairs (47.4%, vs. 8.3% p = 0.004, effect size = 0.44). Also at six months, MCEP children had fewer behavioral symptoms (p = 0.024)) (effect size >0.5); fewer autism symptoms (p = 0.048) (effect size = 0.53); fewer emotional symptoms (p = 0.01) (effect size >0.76); better personal, social skills (p = 0.045) (effect size = 0.51); better executive function (p = 0.032) (effect size = 0.59). Importantly, teachers reported MCEP children showed more improved behavior in the classroom, compared to controls. Discussion This trial was retrospectively registered in the clinicaltrial.gov registry (NCT02970565) on April 9, 2019.